El Olimpo fracturado. La dirección de Julio Scherer García en Excelsior (1968-1976) - Burkholder de la Rosa, Arno (El Colegio de México, A.C., 2010)
This work analyzes the period during which Julio Scherer directed the newspaper Excelsior. After he was expelled in 1976, this period of contemporary Mexican press history  became legendary and has come to be considered  the beginning of a new relationship between the media and the Mexican State. The author  points  out that in order to understand the relevance of Excelsior, it is necessary to know its history from the inside, and establishes that the great dilemma during  Julio Scherer's direction was trying to offer Mexican society a purposeful and democratic journalism from within  an institution characterized by authoritarianism.